Blue light-emitting polyamide and poly(amide-imide)s containing 1, 3, 4-oxadiazole ring in the side chain. (March 2015) - Hamciuc, Corneliu; Hamciuc, Elena; Homocianu, Mihaela; Nicolescu, Alina; Carja, Ionela-Daniela
Abstract: A new diamine monomer containing a 1, 3, 4-oxadiazole ring, 4, 4′-diamino-4″-[2-(4-phenoxy)-5-(4-dimethylaminophenyl)-1, 3, 4-oxadiazole]triphenylmethane, was synthesized and characterized. The diamine is used to prepare novel polyamide and poly(amide-imide)s via a polycondensation reaction with various diacid chlorides in N -methyl-2-pyrrolidone. The structures of the monomers and polymers are characterized by means of FTIR, 1 H, 13 C and 15 N NMR spectroscopy. The polymers result in high yields, and exhibit film forming ability and good solubility in many organic solvents. They show high thermal stability, with decomposition temperature being above 420 °C. The optical properties, absorption and fluorescence characteristics, in solution and solid state, are investigated. Solutions of the polymers exhibit fluorescence in the blue region, having high quantum yield in the range of 38.5–58.1%, and large Stokes shift values (110–120 nm). The introduction of hydrochloric acid into the polymer solutions has a significant effect upon the optical properties. Fluorescence quenching in the presence of 2, 5-dinitrophenol was analysed using Stern–Volmer equation. Graphical abstract: Highlights: A new blue fluorescent diamine having a diphenyloxadiazole group was synthesized. Blue fluorescent polyamide and poly(amide-imide)s with pendant oxadiazole groups were prepared. High quantum yields and large Stokes shifts of the polymer solutions. Fluorescence characteristics were studied in the presence of hydrochloric acid. Fluorescence quenching process was observed in the presence of 2, 5-dinitrophenol.